Magnetic protein aggregates generated by supramolecular assembly of ferritin cages - a modular strategy for the immobilization of enzymes - Ölçücü, Gizem; Wollenhaupt, Bastian; Kohlheyer, Dietrich; Jaeger, Karl-Erich; Krauss, Ulrich (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction Efficient and cost-effective immobilization methods are crucial for advancing the utilization of enzymes in industrial biocatalysis. To this end, in vivo immobilization methods relying on the completely biological production of immobilizates represent an interesting alternative to conventional carrier-based immobilization methods. This study aimed to introduce a novel immobilization strategy using in vivo-produced magnetic protein aggregates (MPAs). Methods MPA production was achieved by expressing gene fusions of the yellow fluorescent protein variant citrine and ferritin variants, including a magnetically enhanced Escherichia coli ferritin mutant. Cellular production of the gene fusions allows supramolecular assembly of the fusion proteins in vivo, driven by citrine-dependent dimerization of ferritin cages. Magnetic properties were confirmed using neodymium magnets. A bait/prey strategy was used to attach alcohol dehydrogenase (ADH) to the MPAs, creating catalytically active MPAs (CatMPAs). These CatMPAs were purified via magnetic columns or centrifugation. Results The fusion of the mutant E. coli ferritin to citrine yielded fluorescent, insoluble protein aggregates, which are released upon cell lysis and coalesce into MPAs. MPAs display magnetic properties, as verified by their attraction to neodymium magnets. We further show that these fully in vivo-produced protein aggregates can be magnetically purified without ex vivo iron loading. Using a bait/prey strategy, MPAs were functionalized by attaching alcohol dehydrogenase post-translationally, creating catalytically active magnetic protein aggregates (CatMPAs). These CatMPAs were easily purified from crude extracts via centrifugation or magnetic columns and showed enhanced stability. Discussion This study presents a modular strategy for the in vivo production of MPAs as scaffold for enzyme immobilization. The approach eliminates the need for traditional, expensive carriers and simplifies the purification process by leveraging the insoluble nature and the magnetic properties of the aggregates, opening up the potential for novel, streamlined applications in biocatalysis.